TAXONOMIC MORPHOLOGICAL STUDY OF Pinus sp. GROWNING IN NORTHERN OF IRAQ. - Haees AL- Jowary; Younis M. Q. AL-alousy; Abdulrazak AL- malah (Mesopotamia Journal of Agriculture)
The  present  work  includes  a  morphological taxonomic  comparative study  of  (6) species belonging to the genus Pinus L. (Pinaceae) which grown in northern  Iraq  in (11) Sites which distributed in Ninavah, Dohuk, and Erbil Provinces, five of them were cultivated (Pinus halepensis Mill., P. eldarica Medw., P. pinea L., P. canariensis Sm., P. radiata Son.) and one species grown naturally( P. brutia Ten.).                                                                                                                    Morphological study includes gross characters, such as (stems, twigs, crown, bark, needle leaves, female cones, seeds, wings of seeds, and indumentums), also characters variation between and within species have been discussed. The species showed clear variation between them, while not varied within species. The study indicates that the stems ,twigs , bark, needle leaves,  female cones, seeds and wings of seeds, showed  a taxonomic importance to identified and separate the species studied ,generally this study indicated that the sexual characteristics (cones) , seeds and wings of seeds are more stable than others characteristics. The method of female cone fulcrum on the branch character showed a large taxonomic importance in contributing to separating species from each other specially in separating and identifying P. brutia for P. halepensis.  Moreover species P. canariensis In most recipes growth and morphological and it was identified and separated from the other species studied.